Chlorogenic Acid and Biohanin A from Trifolium pratense L. Callus Culture Extract: Functional Activity In Vivo - Irina S. Milentyeva; Anna D. Vesnina; Anastasiya M. Fedorova; Elena V. Ostapova; Timothy A. Larichev (Техника и технология пищевых производств)
Polyphenols are potential neuroprotectors that increase lifespan and slow down aging. Red clover (Trifolium pratense L.) is a promising source of biologically active substances. Its extracts contain biochanin A and chlorogenic acid. This research used Caenorhabditis elegans to study the effect of polyphenols extracted from red clover callus cultures on SOD-3 and HSP-16.2 genes, as well as their anti-amyloid potential. The chlorogenic acid and biochanin A (200, 100, 50, and 10 µM) with a purity of 95% were isolated from callus extracts of T. pratense L. The effect of polyphenols on SOD-3 and HSP-16.2 was assessed after 5 and 2 h of heat stress (35°C), respectively, using C. elegans N2 Bristol as model organism. The neuroprotective potential was measured by counting paralyzed nematodes after 18, 40, and 62 h of incubation. The research established a dose-dependent effect between the concentration of biologically active substances and the percentage of paralyzed nematodes after 18 h of cultivation. The lowest paralysis phenotype count occurred at a concentration of 200 μM. The activity of 200 μM biochnin A was 1.18 times as high as that of a 200 μM chlorogenic acid solution. Biochanin A solutions increased SOD-3 expression by 3.7 times, compared to the control. The biologically active substances exhibited relative neuroprotective activity and affected the expression of antioxidant defense gene in C. elegans.